2020
DOI: 10.1016/j.pbb.2020.173037
|View full text |Cite
|
Sign up to set email alerts
|

Influence of n-acetylcysteine maintenance on the pharmacodynamic effects of oral ethanol

Abstract: Rationale Glutamate systems play an important role in the abuse related effects of alcohol. n-Acetylcysteine, a drug that promotes glutamate homeostasis, attenuates a range of alcohol effects in preclinical models. Objectives This human laboratory study determined the influence of n -acetylcysteine maintenance on alcohol self-administration using a model predictive of treatment effectiveness, along with the subjective, performance and physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…The cysteine precursor N -acetylcysteine did not affect alcohol intake and preference in the current study. This is in contrast to reports that show reduced alcohol self-administration upon treatment with N -acetylcysteine in rats ( Quintanilla et al ., 2016 ; Lebourgeois et al, 2018 , 2019 ) and reduced alcohol-related behaviours in clinical samples (Back et al ., 2016; Squeglia et al ., 2018), although negative findings of N -acetylcysteine on alcohol use in humans have also been reported ( Stoops et al ., 2020 ). The discrepancy between our findings and other (pre)clinical reports may be related to methodological differences, in particular voluntary home-cage consumption versus operant-self-administration.…”
Section: Discussionmentioning
confidence: 95%
“…The cysteine precursor N -acetylcysteine did not affect alcohol intake and preference in the current study. This is in contrast to reports that show reduced alcohol self-administration upon treatment with N -acetylcysteine in rats ( Quintanilla et al ., 2016 ; Lebourgeois et al, 2018 , 2019 ) and reduced alcohol-related behaviours in clinical samples (Back et al ., 2016; Squeglia et al ., 2018), although negative findings of N -acetylcysteine on alcohol use in humans have also been reported ( Stoops et al ., 2020 ). The discrepancy between our findings and other (pre)clinical reports may be related to methodological differences, in particular voluntary home-cage consumption versus operant-self-administration.…”
Section: Discussionmentioning
confidence: 95%
“…Alcohol use has been shown to alter the glutamate system. Chronic and binge drinking inhibit glutamate levels and transmission through blockade of NMDA receptors, subsequently leading to elevated glutamate levels during alcohol withdrawal [212][213][214]. N-Acetylcysteine (NAC) is a cysteine prodrug that works to restore glutamatergic tone in reward circuitry by improving the expression and function of the cysteine-glutamate exchanger and normalizing glial glutamate transporters [215,216].…”
Section: N-acetylcysteinementioning
confidence: 99%
“…A secondary analysis of a 12-week, multisite RCT of NAC to treat cannabis use disorder in 277 participants found that NAC increased odds of between-visit abstinence, and reduced alcohol consumption (i.e., drinks per week and drinking days per week) by 30% [ 223 ]. However, a recent 5-day human laboratory study ( N = 9) found that NAC did not attenuate alcohol self-administration [ 212 ]. Additional clinical trials will also examine the effectiveness of NAC in adolescent and adult samples of AUD ([ 224 ], NCT03707951).…”
Section: Pharmacological Treatments For Audmentioning
confidence: 99%
See 1 more Smart Citation
“…One recent example of this failure of translation involves NAC. There is a large literature of positive reports regarding the ability of NAC to decrease reinstatement of drug “seeking” in rodent models (e.g., Moussawi et al, 2009; Reichel et al, 2011; Reissner et al, 2015; Zhou & Kalivas, 2008), yet the clinical efficacy of NAC to reduce drug use or measures of “craving” in human subjects is mixed at best (LaRowe et al, 2013; McClure et al, 2021; Stoops et al, 2020). Another recent example of this translation failure is the 5‐HT2C agonist lorcaserin.…”
Section: Reinstatement and Incubation Of Craving As Models Of Craving...mentioning
confidence: 99%